Gut microbial metabolite trimethylamine N-oxide as a novel predictor for adverse cardiovascular events after PCI: a systematic review and dose-response meta-analysis - Chunyu Zhang; Jinyu He; Yujia Huo; Lin Liu; Yong Xie; Yufei Meng; Gang Wei; Li Deng; Yang Jiang; Jian Feng (Nutrition Journal)
Abstract Background Cardiovascular diseases are the leading cause of mortality worldwide, with acute coronary syndrome (ACS) being particularly fatal. Percutaneous coronary intervention (PCI) is a key treatment for ACS; however, major adverse cardiovascular events (MACE) frequently occur postoperatively. Trimethylamine N-oxide (TMAO), a gut microbiota-derived metabolite, has been proposed as an emerging risk factor for cardiovascular disease. This study aims to systematically evaluate TMAO’s predictive value for MACE post-PCI and explore its dose-response relationship. Methods A comprehensive literature search was conducted in four databases (PubMed, Web of Science, Embase, and the Cochrane Library), including retrospective or prospective cohort studies involving patients undergoing PCI. The primary outcome was MACE, and the secondary outcome was all-cause mortality. A dose-response analysis was conducted using a restricted cubic spline model to explore potential nonlinear associations between TMAO levels and outcomes. Heterogeneity was assessed using the Cochrane Q test and the I² statistic. Subgroup analysis and meta-regression were performed to identify sources of heterogeneity. Results Eleven studies (comprising 13 independent cohorts) with 11,279 participants were included. Pooled analysis showed a significant association between elevated plasma TMAO levels and an increased risk of MACE after PCI (HR: 1.99, 95%CI: 1.68–2.35, 95%PI: 1.64–2.40, I² = 0%, p < 0.00001). Similarly, elevated plasma TMAO levels were significantly associated with an increased risk of all-cause mortality after PCI (HR: 1.76, 95%CI: 1.32–2.35, 95%PI: 0.79–3.90, I² = 65.1%, p < 0.00001). The dose-response analysis did not reveal a nonlinear relationship between TMAO and MACE or all-cause mortality. The linear model showed that each 1 µmol/L increase in plasma TMAO was associated with an 8.95% increased hazard of MACE (HR = 1.0895, 95%CI: 1.03–1.15), while all-cause mortality increased by 4% (HR = 1.04, 95%CI: 0.99–1.09). Conclusions This study demonstrates that elevated plasma TMAO levels are significantly associated with an increased risk of MACE and all-cause mortality after PCI, with a dose-dependent effect on MACE risk. As a potential biomarker, TMAO may be used to predict the risk of adverse cardiovascular events after PCI, and future studies should further validate its clinical utility. Registration PROSPERO CRD42024557486.